BASIC HUMAN NEEDS IN PATIENTS WITH MULTIPLE SCLEROSIS: INTIMACY AND SEXUALITY. - Tesla, Dijana; Mrkonjić, Ružica; Badrov, Tatjana (Central European Journal of Nursing & Midwifery, 2020)
Aim: To analyse the occurrence of sexual dysfunction in patients with multiple sclerosis. Design: A quantitative cross-sectional study. Methods: The study was conducted in cooperation with the Croatian Association of Patients with Multiple Sclerosis, in the form of a questionnaire. A total of 106 patients responded: 24 (23%) male and 82 (77%) female. All subjects were in the age group 21-63 years. Data were analysed using descriptive statistics and the Mann-Whitney test, Kruskal-Wallis test, ANOVA test, and Spearman's rank correlation coefficient. Results: Primary sexual dysfunction (lack of sexual interest and desire), Secondary sexual dysfunction (the occurrence of bladder or urinary symptoms), and Tertiary dysfunction (caused by emotional aspects of MS) were present in most patients. There were no statistically significant differences between subjects within individual categories. Conclusion: Sexual dysfunction is very common among patients suffering from multiple sclerosis, significantly impairing quality of life since sexual and intimate expression are basic human needs which persist in spite of disability or illness. However, patients are reluctant to talk about this highly sensitive issue.